Study of Use of Products and Exposure-Related Behaviors (SUPERB): study design, methods, and demographic characteristics of cohorts - Hertz-Picciotto Irva; Cassady Diana; Lee Kiyoung; Bennett Deborah H; Ritz Beate; Vogt Raea (BMC, 2010)
Abstract Background Exposure to toxic chemicals in the home is a growing concern. This report presents an overview of the recruitment, methods for data collection, instruments used to collect data, and participant demographics for a study examining behaviors that influence exposure to environmental toxins in the home environment, also known as SUPERB (Study of Use of Products and Exposure Related Behaviors). Methods The methods involved three different platforms: telephone interviews, internet-based surveys, and home-based monitoring. The purposes of SUPERB were: first, to compare data collection platforms with regard to feasibility, acceptability and reliability; and second, to provide longitudinal population-based data characterizing seasonal and long-term changes in exposure-related behaviors including food consumption, temporal-spatial activity, and household product use. Results Two cohorts of households were enrolled: families (one parent and one child) from northern California and older individuals (age 55+) from central California. Parents (n = 499) in Northern California families were on average 36 years of age, 47.1% were Latino or nonwhite, and 10.2% took the survey in Spanish. Most of the children enrolled (n = 566) were under 6 years (82.7%). The older adults enrolled (n = 156) were, on average, 66 years of age and 23.7% were Latino or nonwhite, but only 2.6% completed the survey in Spanish. Conclusions We found that oversampling was successful in improving recruitment of under-represented subgroups, such as those with low education, thereby increasing diversity of our study sample. Protocols that minimize participant time, e.g., use of bar scanners and scales rather than questionnaires regarding use of household products, and the implementation of these protocols by staff who built relationships of trust, resulted in high retention over a longitudinal data collection scheme. A relatively small fraction of those who volunteer for longitudinal internet surveys are consistent in filling them out. Future reports will provide critical information on cross-sectional, seasonal and longitudinal patterns of exposure related behaviors in young children, parents of young children, and older adults.